Evicted : poverty and profit in the American city - Desmond, Matthew (Crown Publishers, 2016)
"[The author] takes us into the poorest neighborhoods of Milwaukee to tell the story of eight families on the edge. Arleen is a single mother trying to raise her two sons on the 20 dollars a month she has left after paying for their rundown apartment. Scott is a gentle nurse consumed by a heroin addiction. Lamar, a man with no legs and a neighborhood full of boys to look after, tries to work his way out of debt. Vanetta participates in a botched stickup after her hours are cut. All are spending almost everything they have on rent, and all have fallen behind. The fates of these families are in the hands of two landlords: Sherrena Tarver, a former schoolteacher turned inner-city entrepreneur, and Tobin Charney, who runs one of the worst trailer parks in Milwaukee. They loathe some of their tenants and are fond of others, but as Sherrena puts it, "Love don't pay the bills." She moves to evict Arleen and her boys a few days before Christmas. Even in the most desolate areas of American cities, evictions used to be rare. But today, most poor renting families are spending more than half of their income on housing, and eviction has become ordinary, especially for single mothers. In vivid, intimate prose, Desmond provides a ground-level view of one of the most urgent issues facing America today. As we see families forced into shelters, squalid apartments, or more dangerous neighborhoods, we bear witness to the human cost of America's vast inequality-- and to people's determination and intelligence in the face of hardship. Based on years of embedded fieldwork and painstakingly gathered data, this masterful book transforms our understanding of extreme poverty and economic exploitation while providing fresh ideas for solving a devastating, uniquely American problem. Its unforgettable scenes of hope and loss remind us of the centrality of home, without which nothing else is possible"--Amazon.com.